100 most important women of the 20th century - Markey, Kevin (Des Moines, Iowa : Ladies' Home Journal Books, 1998)
A photo-filled celebration of extraordinary 20th-century women highlights women's contributions in politics, child care, science, education, athletics, literature, entertainment, art, and more. Over 200 photos
Activists & politicians -- Writers & journalists -- Doctors & scientists -- Entrepreneurs -- Artists & entertainers -- Athletes -- Pioneers & adventurers
"Author: Kevin Markey"--P. [4]
Includes index
"Author: Kevin Markey"--P. [4]
Keywords: Women -- Biography; Biography -- 20th century